(untitled) (Journal of Educational Sciences, 2024)
The article is devoted to the study of the problems faced by the authors of domestic monographs on the direction of pedagogical sciences in the process of their publication and popularization. The paper analyzes the data obtained from 42 research participants, including 12 men and 30 women, representing various educational and research institutions. The results of the study showed that the main challenges faced by authors were limited access to publishing houses and platforms for publishing monographs, lack of time to conduct research and prepare materials, and difficulty in selecting appropriate publishers. Difficulties in designing and structuring scholarly materials have also been identified. In the context of popularizing monographs, authors faced low levels of activity in promoting their work. Some authors do not engage in popularization, while others are just beginning to do so. Among the methods of popularization, the most used were the publication of summaries and excerpts in scientific journals, and public lectures on the topic of the monograph. Based on the results obtained, the article offers a number of recommendations for improving the situation. These include developing author support programs, promoting accessibility to publishers and platforms, teaching popularization skills, and using social media to promote monographs. These recommendations are aimed at improving the quality and visibility of domestic monographs in the field of educational sciences. Key words: monograph, popularity, citation, scope, difficulties, promotion.